The R2R3 transcription factor HlMYB8 and its role in flavonoid biosynthesis in hop (Humulus lupulus L.) - Kocábek, Tomáš; Mishra, Ajay Kumar; Matoušek, Jaroslav; Patzak, Josef; Lomnická, Anna; Khare, Mudra; Krofta, Karel (Plant science, 2018)
Hop is an important source of medicinally valuable secondary metabolites including bioactive prenylated chalcones. To gain in-depth knowledge of the regulatory mechanisms of hop flavonoids biosynthesis, full-length cDNA of HlMyb8 transcription factor gene was isolated from lupulin glands. The deduced amino acid sequence of HlMyb8 showed high similarity to a flavonol-specific regulator of phenylpropanoid biosynthesis AtMYB12 from Arabidopsis thaliana. Transient expression studies and qRT-PCR analysis of transgenic hop plants overexpressing HlMyb8 revealed that HlMYB8 activates expression of chalcone synthase HlCHS_H1 as well as other structural genes from the flavonoid pathway branch leading to the production of flavonols (F3H, F'3H, FLS) but not prenylflavonoids (PT1, OMT1) or bitter acids (VPS, PT1). HlMyb8 could cross-activate Arabidopsis flavonol-specific genes but to a much lesser extent than AtMyb12. Reciprocally, AtMyb12 could cross-activate hop flavonol-specific genes. Transcriptome sequence analysis of hop leaf tissue overexpressing HlMyb8 confirmed the modulation of several other genes related to flavonoid biosynthesis pathways (PAL, 4CL, ANR, DFR, LDOX). Analysis of metabolites in hop female cones confirmed that overexpression of HlMyb8 does not increase prenylflavonoid or bitter acids content in lupulin glands. It follows from our results that HlMYB8 plays role in a competition between flavonol and prenylflavonoid or bitter acid pathways by diverting the flux of CHS_H1 gene product and thus, may influence the level of these metabolites in hop lupulin.
Keywords: listy rostlin; R2R3 myb; fylogeneze; Bitter acids; Phylogeny; Amino Acid Sequence; Sequence Alignment; RNA sequencing; stanovení celkové genové exprese; sekvenční seřazení; rostlinné proteiny; Humulus lupulus; Gene Expression Profiling; Plants, Genetically Modified; Nicotiana; Transcription Factors; flavonoidy; transkripční faktory; Chalcone synthase; Plant Leaves; sekvence aminokyselin; Humulus; geneticky modifikované rostliny; Flavonoids; tabák; Plant Proteins